Rozwijanie się Sił Tarcia dla Pewnego Przypadku Współpracy Dwóch Belek - Boliński, B. (Engineering Transactions, 1970)
In this paper the problem of cooperation is considered of two identical beams fixed in a non-deformable support and pressed together by a load of intensity q. A transverse force P applied to the free and of one of the beams causes the evolution of zones between the beams: breaking off, with sliding, and without sliding. Cyclical variations of the force P brings about the formation of hysteresis, which is illustrated in a graph using the system of coordinates: force-bending at point of application of force. In the paper the mechanisms of cooperation are explained and described between the beams for the particular intervals of hysteresis.